X-linked Agammaglobulinemia (XLA) Associated with Progressive Neurodegenerative Syndrome: A Case Report (Bangladesh Journal of Child Health, 2021)
Primary immune deficiency disorders (PIDs) are not an uncommon entity, but the diagnosis is often delayed or even missed due to lack of awareness. Central nervous system involvements due to various reasons are documented in patients with PIDs. This case report describes a 10- year old boy, diagnosed as X-linked agammaglobulinemia (XLA) who developed progressive encephalopathy. He had severe cognitive impairment along with cerebellar and pyramidal dysfunction. MRI of the brain showed generalized cerebral and cerebellar atrophy. Therefore, this boy was diagnosed as a case of XLA with progressive neurodegenerative syndrome.BANGLADESH J CHILD HEALTH 2021; VOL 45 (1) : 55-58